Ways of Using the Karakalpak Oral Folk Art in the Upbringing of the Future Generation - Zarimbetova Gulzira Kosherbaevna (Researchparks Publishing, 2021)
This article discusses the formation of Karakalpak folk traditions and customs, their place in public life. Traditions are a type of feature that distinguishes people from other peoples, showing their mental peculiarity and the level of cultural development.